2012
DOI: 10.1155/2012/390758
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Analysis of a Pyroprocessing Coupled SFR Fuel Recycling

Abstract: Numerous studies have attempted to solve the problems constraining the sustainable utilization of nuclear power, for example, the already accumulated HLWs, the worsening environment due to greenhouse emissions, the questionable reliability of natural uranium resources, and the argument over nuclear safety, which are certainly top issues to be addressed. A well-organized nuclear fuel cycle system is the basis for nuclear power sustainability. Therefore, which type of reactor to be employed and whether or not to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 8 publications
0
14
0
Order By: Relevance
“…It was also assumed that the metallic SNF discharged from SFRs will be recycled in the Pyro-SFR fuel cycle based upon past reference studies [12,13,31].…”
Section: Establishment Of Strategic Scenarios For Transmutation Ofmentioning
confidence: 99%
See 4 more Smart Citations
“…It was also assumed that the metallic SNF discharged from SFRs will be recycled in the Pyro-SFR fuel cycle based upon past reference studies [12,13,31].…”
Section: Establishment Of Strategic Scenarios For Transmutation Ofmentioning
confidence: 99%
“…The impact of CR on the SFR was determined by the consumption of TRUs as it is reported that the SFR with higher CR burns less TRUs, while the SFR with lower CR transmutes more. Thus, the minimum number of SFRs to be deployed for transmutation of all the inventory of TRUs can be eventually decided by the value of CR of a specific SFR design [13,[33][34][35]. …”
Section: Establishment Of Strategic Scenarios For Transmutation Ofmentioning
confidence: 99%
See 3 more Smart Citations